Senegal : Third and Fourth Reviews Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper focuses on Senegal's Third and Fourth Reviews Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and Request for Waiver of Performance Criteria. Program implementation in 2005 was uneven. Most performance criteria (PCs) for the third and fourth reviews were met, except for the continuous PCs on the arrears of, and budgetary transfers to, the state electricity company, and the ceiling on no-bid public contracts. On the basis of the corrective actions taken and planned, the authorities requested waivers for the missed PCs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet